The Portrait of Qiong Yao’s Life in Her Novels - Cendrawaty Cendrawaty; Yovita Yovita; Juniwati Juniwati (Bina Nusantara University, 2009)
Qiong Yao was a well known woman author and a film director in Taiwan who had written more than 60 love novels, that had been developed into famous films. This paper aims to explore Qiong Yao’s biography related to her works. Library research was done by dividing Qiong Yao’s works into several themes, and then analysing their novels’ theme and her life. It can be concluded that her permanent theme is love. In her novels, she scatters love that is able to touch her readers as well as film viewers. And, this love theme is closely related to her life.